Long Term Relationships between Open Skies Agreements and Passenger Flight Schedules between US and Europe - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2009)
This paper examines the long term impact of open skies agreements between US and Europe from the perspective of scheduled passenger flights. Our analysis is based on flight schedule data from the Official Airline Guide and also includes bilateral trade volume data and crude oil prices. We find that the changes in frequency, in total capacity (in terms of number of seats per week) and in inter-city connectivity (in terms of number of cities and city-pairs served) are more complex than the conventional notion of an abrupt, monotonic increase in air transport services between countries that have bilateral open skies agreements compared to those without. The results of this study would help temper the expectations of policy makers from open skies agreements. They would also have implications on possible transatlantic airline mergers.